Valuation of benefits for Giant Panda conservation by local community in the proximity of Zoo Negara, Malaysia - Mohd Rosli, Muhammad Syukran (2019)
The Giant Panda (Ailuropoda melanoleuca) is an endangered endemic species in China and a world symbol for conservation and preservation. The arrival of giant panda in Malaysia is seen as an opportunity to undertake research on the animals which could benefit conservation of captivate wildlife in general. The giant pandas that are placed in the million-ringgit complex at Zoo Negara Malaysia have attracted influx of visitors to the zoo. Giant Panda Conservation Centre (GPCC) generates mixed reactions among the communities living in the proximity of the zoo. The giant panda attraction gives an extensive variety of biological community services to human prosperity, but the value that could benefit the local communities is unknown. The purpose of this research is to estimate the benefit of giant panda conservation among local community. A total of 250 respondents were selected at the vicinity of Majlis Perbandaran Ampang Jaya, Majlis Perbandaran Selayang and Dewan Bandaraya Kuala Lumpur. The findings indicated that local community is willing to pay for giant panda conservation about RM13.47, meanwhile the conservation value was estimated at RM36,318,218.10 for the year 2016. Moreover, the results found that the factors influenced the WTP are monthly income, household size, male gender, and perception. The findings of this research would also be useful to estimate economic valuation and outline the benefits of giant panda conservation as perceived by local community in Malaysia.